Behavioral Intentions toward the Adoption of Halal Auditing Mobile Apps in Malaysia - Hamdan, Nur Aaina Athira; Mohamad Husny Hamid, Zuhra Junaida; Illyas, Mohd. Iskandar; Jamaian, Siti Suhana (Ijriss, 2025)
Obtaining halal certification is essential for companies to establish consumer trust in their products. However, the traditional, manual certification process poses significant challenges for halal auditors due to the extensive time needed to prepare checklists and complete applications. While technological advancements have transformed many industries, the halal sector, particularly the certification process, has seen limited adoption of these innovations. Nevertheless, some auditors are open to using technology to streamline their work. This study investigates the factors influencing the adoption of mobile auditing applications for halal certification using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The model examines eight factors: performance expectancy, effort expectancy, social influence, facilitating conditions, attitude toward technology, self-efficacy, anxiety, and behavioural intention. The study surveyed 552 users of mobile auditing apps in halal certification processes. Findings indicate that direct factors: performance expectancy, effort expectancy, social influence, facilitating condition and indirect factors: self-efficacy and attitude towards using the technology positively impact the intention to adopt these applications.